THE DISCRETION OF THE POLICE TO ALLEVIATE THE ACT OF ANARCHY IN THE SOCIETY - Joko Rudiantoro (Fakultas Hukum Universitas Mataram, 2014)
Indonesian Police is a state apparatus that plays a role to maintain public security and order,to enforce the law and to provide protection, assistance, and service to the community in termsof maintaining internal security in accordance with the Article 5 of Act No. 2 of 2002 on thepolice. Police discretion is an authority given to the police, to take decisions in certain situationsthat require separate consideration and a matter of moral and located within the boundariesbetween law and morals. Benchmark for police officers to use discretionary authority in dealingwith anarchy in society, is based on statute approach through conceptual approach which isbased on (Case Approach) in the field, such as the emergency condition, for the sake of publicinterest, in terms of self-defending or defending others, and in terms of defending slef-respect orown property.Keywords : Police, Discretion